The Mental Dictionary and Teaching and Learning The Arabic Language: A Didactic-Cognitive Linguistic Approach - Alaoui, Mohamed Ismail (Universitas Ahmad Dahlan, 2023)
Cognitive linguistics has become an essential reference for many specialists and researchers in teaching and learning languages. This is in building their educational curricula and developing their linguistic research. It aims to analyze and treat linguistic aspects related to the human brain through research into the conceptual structures of meaning, mental perception, the processes controlling thinking, and the internal organization of the mental lexicon. This library research analyzes the mental dictionary in the Arabic learning context using a deductive-cognitive linguistic approach. The results show ten weights and activating the mental lexicon among learners that can be used in Arabic learning. Furthermore, the study reveals learning strategies for activating the mental lexicon.